MEMBUMIKAN PESAN DAMAI AL-QUR’AN (AS-SALÁM) SEBAGAI MEDIATOR KOMUNIKASI BANGSA - Egi Tanadi Taufik; Dzalfa Farida Humaira (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2020)
Various conflict transformation through shows that the message of peace has entered a transitional phase that is quite prospective in the Indonesian Islamic societies. On the other hand, the phenomenon of the